From empire to union conceptions of German constitutional law since 1871 - Murkens, Jo Eric. (Oxford : Oxford University Press, 2013)
Examining the modern development of German constitutional thought, this book traces the key public law concepts of state constitution, sovereignty, and democracy from their emergence in the 19th century through to the present day. It analyses the fraught constitutional relationship between Germany and the EU from a sociological perspective.
Description based on online resource; title from home page (viewed on Mar. 12, 2013).
Includes bibliographical references and index.
Keywords: Constitutional law -- Germany; Constitutional law -- Germany -- History; Law -- European Union countries -- International unification